2021
DOI: 10.3390/genes12040498
|View full text |Cite
|
Sign up to set email alerts
|

Causal Associations between Serum Urea and Cancer: A Mendelian Randomization Study

Abstract: Urea is largely derived from the urea cycle reactions through hepatic detoxification of free ammonia and cleared by urination, and the serum urea level is a crucial medical indicator for measuring the kidney function in patients with nephropathy; however, investigative revelations pointing to the serum urea level as a risk factor for cancer are very scarce, and relevant studies are restricted by potential biases. We aimed to explore the causal relationships of the serum urea level with cancer development by fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
8
4
Order By: Relevance
“…While absolute monocytes count was identified as a potential prognostic factor for breast cancer 54 , the association of red blood cell count with breast cancer has not been studied explicitly. Plasma urea, a blood biomarker related to kidney function, was reported to have null causal relationship with breast cancer 55 , but our study suggests it may be associated with breast cancer. Aspartate aminotransferase and alkaline phosphatase are both blood biomarkers related to liver function and were not previously associated with non-metastatic breast cancer 56 .…”
Section: Discussioncontrasting
confidence: 74%
“…While absolute monocytes count was identified as a potential prognostic factor for breast cancer 54 , the association of red blood cell count with breast cancer has not been studied explicitly. Plasma urea, a blood biomarker related to kidney function, was reported to have null causal relationship with breast cancer 55 , but our study suggests it may be associated with breast cancer. Aspartate aminotransferase and alkaline phosphatase are both blood biomarkers related to liver function and were not previously associated with non-metastatic breast cancer 56 .…”
Section: Discussioncontrasting
confidence: 74%
“…The risk of getting colon cancer in a first-degree relative was 2.2, which drops to 1.3 and 1.2 in second and third-degree relatives 51 , suggesting a strong familial genetic component. Whereas pulse and urea had minor contributions to the risk, emphasizing the modest but key role of cardiovascular 52 and renal health 53 in CRC development 53 . Finally, self-reported poor health was a strong classifying feature, previously linked to overall cancer risk and all-cause mortality 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Urea is largely derived from the urea cycle reactions through hepatic detoxification of free ammonia and cleared by urination. Recently, study revealed that an intriguing link between serum urea and cancer risks ( 20 ). Previous study reported that serine/threonine kinase 2 promotes proliferation can be used to predict metastasis and poor prognosis in NSCLC ( 21 ).…”
Section: Discussionmentioning
confidence: 99%